Effects of Molecular Numbers and Time Steps on the Estimation of Diffusion Coefficients in Molecular Dynamic Simulation - LIU, QINGZHI (Asian Journal of Chemistry, 2010)
Using molecular dynamics simulation, the diffusions of glycine, methane, ammonia and carbon dioxide in water were simulated in the canonical NVT ensemble. This study shows that the molecular number of the sample and the time step used are two important factors for the simulation. The diffusion coefficients increase with increasing molecular numbers and gradually approach to the experimental value. When two samples are big enough that their difference is not obvious, the sample with smaller molecules should be applied. Time step also plays a significant role in the estimation of diffusion coefficients. The estimated diffusion coefficients increase with time step and reach maximum before they start to decline. This paper suggests several time steps between 0.1 fs to 1.5 fs be taken in the simulation of a special system and take 70 % of the time step corresponding to maximal diffusion coefficient value as the reasonable time step.